Medical students' perspectives about distance learning during early COVID 19 pandemic: a qualitative study - Muhammad Reza Utama; Yelvi Levani; Ayu Lidya Paramita (Universitas Muhammadiyah Surabaya, 2020)
Background: Medical education throughout the world has experienced major changes as a consequence of the presence of the COVID-19 pandemic. The Government of Indonesia has instructed physical distancing so that teaching and learning activities, including in the Faculty of Medicine, must be carried out at home with online methods to reduce the risk of COVID distribution. Objective: to explore undergraduate medical students’ perspectives towards distance learning during early COVID 19 pandemic at Muhammadiyah Surabaya University - Faculty of Medicine (MSU-FM), Indonesia. Methods: a qualitative study of students’ online survey responses had been done. Thematic analysis based on Unified Theory of Acceptance and Usage of Technolgy (UTAUT) constructs was done to ecplore students’ perspectives. Results: Students have a positive perspective related to performance expectancy of distance learning. This factor have been perceived as factor that support the behavior of the use of distance learning in order to increase cognitive involvement in the learning process. However, in this study, other factors conveyed by students limiting their optimal use of current distance learning platform. Conclusion: Students‘ user experiences must be developed and maintained continuously during this pandemic era. Longitudinal studies that investigate the long-term impact of various distance learning platforms‘ usage also need further study.